2007
DOI: 10.1016/j.juro.2007.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Hypospadias With Severe Chordee: Single Stage Repair Using Corporeal Tunica Vaginalis Free Graft

Abstract: In this preliminary report the majority of patients with proximal hypospadias and severe chordee were successfully treated with single stage repair using tunica vaginalis free graft for correction of severe chordee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Recently, Kajbafzadeh et al [8] reported UP elevation, ventral corporotomy with tunica vaginalis grafting, and TIP urethroplasty as a single-stage operation for 13 proximal hypospadias cases. With mean follow up of 27 months there was one case of residual VC < 20 and one fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kajbafzadeh et al [8] reported UP elevation, ventral corporotomy with tunica vaginalis grafting, and TIP urethroplasty as a single-stage operation for 13 proximal hypospadias cases. With mean follow up of 27 months there was one case of residual VC < 20 and one fistula.…”
Section: Discussionmentioning
confidence: 99%
“…13 Severity of ventral penile curvature is also associated with an increased complication rate. 15 In our study we found a total of 55 cases with varying degree of chordee, of which 3.6% of mild, 38.8% of moderate and 35.7% of severe cases had complications (p = 0.0001). The degree of curvature was directly proportional to severity of (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…We did only spongioplasty as water proofing, but others have used tunica vaginalis to reduce the complication in proximal hypospadias. 15 We recommend using additional dartos or tunica vaginalis to prevent complications in poorly developed spongiosum patients.…”
Section: Discussionmentioning
confidence: 99%
“…They are also easy to be cultured in vitro and the commonly used DMEM medium could satisfy their nutritional requirement [10,11]. Mesothelium-lined grafts including peritoneum [12,13] and tunica vaginalis [14,15] have already been attempted in urethral reconstruction with good results. In our previous study, we successfully used a kind of mesothelium-lined autologous tubular tissue as urethral graft [16].…”
Section: Discussionmentioning
confidence: 99%